2013
DOI: 10.1371/journal.pone.0075316
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Variations in Maternal Provisioning of Crepidula fornicata (Gastropoda): Fatty Acid Composition of Females, Embryos and Larvae

Abstract: Recruitment success of marine invertebrate populations not only depends on the number of recruits but also on their quality which affects their survival. In species characterized by a mixed development (encapsulated embryonic development and release of planktotrophic larvae), the offspring quality depends on both maternal provisioning and larval feeding. Here, we investigated potential changes of maternal provisioning over the whole reproductive period in a gastropod with a mixed development: Crepidula forn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 98 publications
1
13
0
2
Order By: Relevance
“…As shown earlier with SI, all ontogenic stages of C. fornicata may have probably exploited SSOM before the spring bloom when food in the water column is less available. In this pool of OM, FA revealed that slipper limpets likely fed on benthic diatoms (as suggested by 16:1n-7 and 20:5n-3; Dunstan et al 1992;Napolitano et al 1997;Passarelli et al 2012), dinoflagellates (22:6n-3;Zhukova and Aizdacher 1995;Lavaud et al 2018) and bacteria (Branched FA and 18:1n-7;Perry et al 1979;Zhukova et al 1992;Haack et al 1994), which is in agreement with previous interpretations done in other comparable coastal bays Leroy et al, 2013). In sediment, bacteria are often associated with detritus and are therefore not considered as a high-quality food source (Dalsgaard et al, 2003).…”
Section: Trophic Niche Of C Fornicata In Relation To Ontogenic Changessupporting
confidence: 92%
See 1 more Smart Citation
“…As shown earlier with SI, all ontogenic stages of C. fornicata may have probably exploited SSOM before the spring bloom when food in the water column is less available. In this pool of OM, FA revealed that slipper limpets likely fed on benthic diatoms (as suggested by 16:1n-7 and 20:5n-3; Dunstan et al 1992;Napolitano et al 1997;Passarelli et al 2012), dinoflagellates (22:6n-3;Zhukova and Aizdacher 1995;Lavaud et al 2018) and bacteria (Branched FA and 18:1n-7;Perry et al 1979;Zhukova et al 1992;Haack et al 1994), which is in agreement with previous interpretations done in other comparable coastal bays Leroy et al, 2013). In sediment, bacteria are often associated with detritus and are therefore not considered as a high-quality food source (Dalsgaard et al, 2003).…”
Section: Trophic Niche Of C Fornicata In Relation To Ontogenic Changessupporting
confidence: 92%
“…They are energy reserves (neutral lipids) but also key structural component of cell membranes (polar lipids). In molluscs as for C. fornicata, such lipids storages are essential for larval development and during mature ontogenic stages for gonadal development (Deslous-Paoli and Héral, 1986;Leroy et al, 2013). Contrary to polar lipids, FA incorporated in the neutral fraction are directly mobilized and reflect more closely the FA composition of the diet (Fernández-Reiriz et al, 2015;Jezyk and Penicnak, 1966;Langdon and Waldock, 1981;Waldock and Nascimento, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…Adult females were removed from their substrates to check for incubating egg capsules. Capsules with larvae that were ready to hatch (stage IV veligers sensu Leroy et al, 2013 ) were selected and hatched by physically agitating them in a bowl of filtered seawater at room temperature. Larvae from three females were combined for rearing in cultures of 800 ml of 1 µm-filtered seawater (FSW) at a concentration of one larva per four ml.…”
Section: Methodsmentioning
confidence: 99%
“…Идентификация метиловых эфиров жирных кислот. Идентификация МЭЖК выполнена в ЦКП «Спектрометрия и хроматография» ФИЦ ИнБЮМ на газовом хроматографе Кристалл 5000.2 (ЗАО СКБ «Хроматэк», г. Йошкар-Ола, РФ) с квадрупольным масс-детектором и капиллярной колонкой DB-5ms (Agilent Technologies) длиной 30 м, с внутренним диаметром 0, 25 1,4 ± 0,6 0,6 ± 0,3 1,3 ± 0,4 1,0 ± 0,3 1,4 ± 0,5 Миристиновая (тетрадекановая) (C14:0) 6,2 ± 0,2 5,7 ± 0,6 7,7 ± 0,7 6,4 ± 0,4 6,5 ± 0,6 Пентадекановая (пентадециловая) (C15:0) 4,4 ± 0,8 5,3 ± 1,1 8,5 ± 0,5 5,8 ± 0,2 4,7 ± 0,7 Пальмитолеиновая (цис-9-гексадеценовая) (C16:1ω7) 11,0 ± 0,6 6,8 ± 0,6 7,0 ± 0,2 9,6 ± 0,4 10,8 ± 0,8 Пальмитиновая (гексадекановая) (C16:0) 29,3 ± 4,3 33,8 ± 0,4 30,1 ± 0,3 34,7 ± 0,6 31,7 ± 2,3 цис-10-гептадеценовая (C17:1ω7) 3,9 ± 1,5 1,2 ± 0,4 1,2 ± 0,2 1,4 ± 0,4 2,4 ± 1,5 14-метилгексадекановая (антеизо-C17:0) 2,4 ± 0,5 1,8 ± 0,3 2,3 ± 0,2 2,0 ± 0,1 2,6 ± 0,8 Арахидоновая (цис,цис,цис,цис-5,8,11,14эйкозатетраеновая) (C20:4ω6)…”
Section: материал и методыunclassified
“…Концентрация незаменимой арахидоновой (C20:4ω6) кислоты в трохофорах не являлась постоянной величиной и варьировала в широком диапазоне от 1 до 21 %. Для сравнения: в гастроподах концентрация арахидоновой (C20:4ω6) кислоты достигала 5,73 % [25]. Как известно, живые организмы могут синтезировать арахидоновую (C20:4ω6) кислоту из незаменимой Омега-6-ненасыщенной линолевой кислоты [1].…”
Section: материал и методыunclassified